Interface Analysis of Bullying Monitoring Systems for Students in Avicena Rajeg School - Sunandar, Endang; Fauzan, Jimmy; Sunarya, Po Abas; Rafika, Ageng Setiani (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
The Emergency Panic Button tool has been developed to provide quick response and accessibility in emergency situations. In this research, we designed and developed an Emergency Panic Button tool using the Arduino ESP32 Devkit V1. This tool allows users to easily trigger emergency signals, send help messages to Telegram, and includes user location information and monitoring of the user's body temperature. The development method includes the integration of electronic components such as buttons, communication modules such as GSM or Wi-Fi, and body temperature sensors. We use Arduino ESP32 Devkit V1 as the main platform and utilize the Telegram API software to send help messages to specified contacts. In this research, we study the theoretical foundations related to emergency systems, Arduino technology, integration with the Telegram API, and user body temperature training. We design and implement tools by developing Arduino programs that allow training panic buttons, sending emergency messages to Telegram, acquiring locations using GPS modules or other methods, as well as training the user's body temperature using temperature sensors.